2006
DOI: 10.1245/s10434-006-9058-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgery in Recurrent Ovarian Cancer: The Arbeitsgemeinschaft Gynaekologische Onkologie (AGO) DESKTOP OVAR Trial

Abstract: Only complete resection was associated with prolonged survival in recurrent ovarian cancer. The identified criteria panel will be verified in a prospective trial (AGO-DESKTOP II) evaluating whether it will render a useful tool for selecting the right patients for cytoreductive surgery in recurrent ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
212
0
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(239 citation statements)
references
References 27 publications
9
212
0
14
Order By: Relevance
“…A combination of PS, early FIGO stage initially or no residual tumor after first surgery, and absence of ascites could predict complete resection in 79 % of patients. [21] The DESKTOP 2 study prospectively analyzed the predictive value of 3 of these criteria (complete resection at first surgery, good performance status, and absence of ascites and found that when all 3 are met complete cytoreduction can be achieved in 79 % of the patients with a morbidity of 11 %. [22] These criteria exclude a subgroup of patients who never had surgery by a gynecologic oncologist/ surgical oncologist and hence have had an incomplete CRS.…”
Section: For Recurrent Ovarian Cancermentioning
confidence: 99%
“…A combination of PS, early FIGO stage initially or no residual tumor after first surgery, and absence of ascites could predict complete resection in 79 % of patients. [21] The DESKTOP 2 study prospectively analyzed the predictive value of 3 of these criteria (complete resection at first surgery, good performance status, and absence of ascites and found that when all 3 are met complete cytoreduction can be achieved in 79 % of the patients with a morbidity of 11 %. [22] These criteria exclude a subgroup of patients who never had surgery by a gynecologic oncologist/ surgical oncologist and hence have had an incomplete CRS.…”
Section: For Recurrent Ovarian Cancermentioning
confidence: 99%
“…Other key eligibility criteria included Eastern Cooperative Oncology Group (ECOG) performance status of 0-2 23 ; adequate bone marrow, coagulation, and renal (creatinine 1.5 3 institutional upper limit of normal) and hepatic function; signed informed consent; and deemed resectable to no visible residual disease by the investigator based on selection criteria for secondary cytoreductive surgery. [24][25][26] Patients were ineligible if they met any of the following exclusion criteria: pre-existing neuropathy (National Cancer Institute Common Toxicity Criteria for Adverse Events [NCI-CTCAE] version 3.0) grade >1; known platinum allergy; borderline histology; and other serious disabling diseases that would contraindicate secondary cytoreductive surgery followed by postoperative platinum-based IV chemotherapy.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…However, the criteria for SDS candidacy have not fully established; therefore, the benefit of surgery for patients with relapsed ovarian cancer may be limited (13). Recently, selection criteria for operable patients with recurrent ovarian cancer were suggested by the DESKTOP trial: i) Good PS, ii) no or small volume of ascites at recurrence, and iii) no gross residual disease after primary surgery (14). Another study suggested that the predictive factors for complete resection at SDS included FIGO stage, complete primary surgery, PFI, PS, CA125 value at recurrence and ascites at recurrence (15).…”
Section: Long-term Short-term Survivors N (%) Survivors N (%) -----mentioning
confidence: 99%